Analysis of the Content of Foreign Labor use Regulations Against Indonesia’s Labor Protections. - Siti Kunarti (Jurnal Dinamika Hukum, 2020)
Globalization moves people indefinitely and includes working in other countries, and accepting foreign workers because it wants the free movement of labor (pree personal movement) over the territorial boundaries of the country. The research is aimed at reviewing and analyzing the content of foreign labor use regulations in Indonesia and whether the content of foreign labor regulations has protected Indonesian workers. The research method used in this study is normative juridical with a statute approach, comparative approach, history approach. The results showed that the Development of Foreign Workers (TKA) Usage Arrangements in Indonesia since Indonesia became independent is regulated in the form of a separate law namely Law No. 3 of 1958 on the Placement of Foreign Workers and subsequently, the Regulation of foreign workers is included in several employment laws, and finally in CHAPTER VI Article 42-49 law No. 13 of 2003 on Employment. The content of the arrangement of the use of foreign labor has not fully provided protection and legal certainty, the revocation of the mandatory Indonesian language requirements for foreign workers is a form of discrimination, as well as the need for strict requirements and qualifications for foreign workers entering Indonesia are skilled, making it possible for the transfer of expertise and technology, supporting economic development, and encouraging the improvement of the competence of the Indonesian workforce. Keywords: Charge Settings, Foreign Labour, Protection .